Which children account for repeated admissions within 1 year in a Brazilian pediatric intensive care unit? - Paulo Sérgio Lucas da Silva; Marcelo Cunio Machado Fonseca (Elsevier, 2019)
Objective: While studies have focused on early readmissions or readmissions during the same hospitalization in a pediatric intensive care unit, little is known about the children with recurrent admissions. We sought to assess the characteristics of patients readmitted within 1 year in a Brazilian pediatric intensive care unit. Methods: This was a retrospective study carried out in a tertiary pediatric intensive care unit. The outcome was the maximum number of readmissions experienced by each child within any 365-day interval during a 5-year follow-up period. Results: Of the 758 total eligible admissions, 75 patients (9.8%) were readmissions. Those patients accounted for 33% of all pediatric intensive care unit bed care days. Median time to readmission was 73 days for all readmissions. Logistic regression showed that complex chronic conditions (odds ratio 1.07), severe to moderate cognitive disability (odds ratio 1.08), and use of technology assistance (odds ratio 1.17) were associated with readmissions. Multiple admissions had a significantly prolonged duration of mechanical ventilation (8 vs. 6 days), longer length of pediatric intensive care unit (7 vs 4 days) and hospital stays (20 vs 9 days), and higher mortality rate (21.3% vs 5.1%) compared with index admissions. Conclusion: The rate of pediatric intensive care unit readmissions within 1 year was low; however, it was associated with a relevant number of bed care days and worse outcomes. A 30-day index of readmission may be inadequate to mirror the burden of pediatric intensive care unit readmissions. Patients with complex chronic conditions, poor functional status or technology assistance are at higher risk for readmissions. Future studies should address the impact of qualitative interventions on healthcare and recurrent admissions. Resumo: Objetivo: Apesar dos estudos terem focado em reinternações precoces ou reinternações durante a mesma internação na unidade de terapia intensiva pediátrica, pouco se sabe sobre essas crianças com internações recorrentes. Buscamos avaliar as características dos pacientes reinternados em 1 ano em uma unidade de terapia intensiva pediátrica brasileira. Métodos: Este foi um estudo retrospectivo realizado em uma unidade de terapia intensiva pediátrica terciária. O resultado foi o número máximo de reinternações por cada criança em qualquer período de 365 dias durante um período de acompanhamento de 5 anos. Resultados: Do total de 758 internações elegíveis, 75 pacientes (9,8%) foram de reinternações. Esses pacientes representaram 33% de todos os dias de cuidados com os internados na unidade de terapia intensiva pediátrica. O tempo mediano para a reinternação foi 73 dias para todas as reinternações. A regressão logística mostrou que as doenças crônicas complexas (razão de chance de 1,07), deficiência cognitiva grave a moderada (razão de chance de 1,08) e uso de suporte de aparelhos tecnológicos (razão de chance de 1,17) foram associados às reinternações. As múltiplas internações apresentaram duração significativamente prolongada na ventilação mecânica (8 em comparação a 6 dias), maior tempo de internação na unidade de terapia intensiva pediátrica (7 em comparação a 4 dias) e tempos de internação (20 em comparação a 9 dias) e maior taxa de mortalidade (21,3% em comparação a 5,1%), em comparação às internações iniciais. Conclusão: A taxa de reinternações na unidade de terapia intensiva pediátrica em 1 ano foi baixa, porém foi associada a um número relevante de cuidados durante internação e piores resultados. Um índice de reinternação de 30 dias pode ser inadequado para refletir a grande número de reinternações na unidade de terapia intensiva pediátrica. Os pacientes com doenças crônicas complexas, estado funcional ruim ou suporte de aparelhos tecnológicos correm maior risco de reinternações. Estudos futuros devem abordar o impacto das intervenções qualitativas sobre os serviços de saúde e as internações recorrentes. Keywords: Children, Hospitalization, Outcome, Pediatric intensive care unit, Readmission, Palavras-chave: Crianças, Internação, Resultado, Unidade de terapia intensiva pediátrica, Reinternação